Professional Vision and the Compensatory Effect of a Minimal Instructional Intervention: A Quasi-Experimental Eye-Tracking Study With Novice and Expert Teachers - Grub, Ann-Sophie; Biermann, Antje; Lewalter, Doris; Brünken, Roland (Frontiers in Education, 2022)
The early recognition of potential disruptions in learning environments is of great importance for the proactive control of the teaching process and maximizing learning outcomes. The professional competence of (prospective) teachers is required for successful classroom management. Teachers’ professional vision (PV) serves as a link between their knowledge and classroom management behavior. Expertise research in different domains has shown that experts and novices show differences in visual perception based on their expertise level; however, research results to date are heterogeneous and often based on small samples. An eye-tracking study using a quasi-randomized experimental design was performed to investigate how German prospective (n=29) and experienced (n=35) teachers perceived different teaching situations. The goal of the study was to determine whether previous results from expertise research could be replicated in a standardized experimental setting. Moreover, the impact of a minimal intervention (specific instruction) on PV of potential classroom disruptions was investigated. In contrast to the hypotheses, no expertise-dependent differences on various eye-tracking parameters can be found. Furthermore, the minimal intervention does not lead to an improvement in PV for experts or novices. The results are discussed with regard to the discrepancy with previously published findings and possible explanations are offered (e.g., the salience of disruptions, internal personal factors, external environmental influences).